Weldability of AA5083-O/H111 and naval GL D36 steel lap joints by friction stir welding - Batistão, Bruna Fernanda (Universidade Federal de São Carlos, 2021)
Steel structures welded with aluminum alloys, which combine the low cost and high mechanical strength of steel with the weight reduction and the excellent specific properties of the aluminum alloys, are in great demand. In this context, Friction Stir Welding (FSW) stands out because it reaches lower temperatures during the welding process, reducing the thickness of the Intermetallic Compound (IMC) layers formed. Based on this, the present work proposed the application of the FSW technique to weld AA55083-O/H111 aluminum alloy to Naval GL D36 steel in lap joint configuration. For this, the influence of the welding parameters (welding speed from 5 mm/s to 15 mm/s and rotational speed from 300 rpm to 1100 rpm) on the microstructure, interface, and mechanical properties was analyzed. Joints without voids or defects were produced using low welding speeds (5 mm/s and 7 mm/s) and intermediate rotational speeds (500 rpm, 700 rpm and 900 rpm). It was observed that the decrease in the rotational speed or increase in the welding speed resulted in scattered voids and tunnel defects, a reduction in the grain size of the aluminum stir zone to a minimum of 4.04 um (5 mm/s and 300 rpm), and, consequently, an increase of the microhardness in this zone to a maximum of 100 HV0.2 (5 mm/s and 300 rpm). The maximum microhardness of 662 HV0.2 was obtained in the interface, due to the presence of the FeAl and Fe3Al IMC layers, which increased in thickness with the increasing of the welding speed and rotational speed. A combination of thinner IMC layers, higher steel hooks height, and micro interlocks in the weld interface resulted in better mechanical properties, achieving a maximum average lap shear strength load of 16.98 kN.
Soldabilidade de juntas de sobreposição de AA5083-O/H111 e aço naval GL D36 por soldagem por fricção e mistura
Keywords: Ligas de alumínio; Aço; Soldagem por fricção e mistura; Construção naval; Configuração de junta de sobreposição; Aluminum alloys; Steel; Friction stir welding; Shipbuilding; Lap joint configuration; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA